PENGARUH MEDIA DAN GROUP INFLUENCE TERHADAP ATTITUDES KONSUMEN WANITA GENERASI Y PADA PRODUK KECANTIKAN DENGAN SUBJECTIVE NORMS SEBAGAI VARIABEL MEDIASI - Yasmine, Almira; Prasastyo, Klemens Wedanaji (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
The purpose of this study is to identify the impact of media and group influence on female consumers of generation Y’s attitudes towards beauty products with subjective norms as mediation variables. In this study, samples were collected by conducting non-probability sampling and purposive sampling techniques. The obtained data were based on the responses of 310 respondents which were submitted through an online questionnaire. The analytical method used to process the data was structured equation modelling (SEM) using WarpPLS 7.0. The result of this study shows that media and group influence give positive and significant impact on subjective norms, and subjective norms also give positive and significant impact on attitudes. Subjective norms do not mediate the impacts of media influence on attitudes. On the other hand, subjective norms partially mediate the impact of group influences on attitudes.